The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1177/20552173221103436
|View full text |Cite
|
Sign up to set email alerts
|

Continuous monitoring with wearables in multiple sclerosis reveals an association of cardiac autonomic dysfunction with disease severity

Abstract: Background Dysfunction of the autonomic nervous system is common in multiple sclerosis patients, and probably present years before diagnosis, but its role in the disease is poorly understood. Objectives To study the autonomic nervous system in patients with multiple sclerosis using cardiac autonomic regulation measured with a wearable. Methods In a two-week study, we present a method to standardize the measurement of heart rate variability using a wearable sensor that allows the investigation of circadian tren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…109 . Hilty et al found an association between heart rate variability and disease severity in PwMS through 24-hour monitoring with a wearable device 110 . During a virtual peg insertion test, smoothness and grip force measured with a haptic device were altered in PwMS compared to HC and showed higher sensitivity than its clinical counterparts 111 .…”
Section: Other Wearablesmentioning
confidence: 99%
“…109 . Hilty et al found an association between heart rate variability and disease severity in PwMS through 24-hour monitoring with a wearable device 110 . During a virtual peg insertion test, smoothness and grip force measured with a haptic device were altered in PwMS compared to HC and showed higher sensitivity than its clinical counterparts 111 .…”
Section: Other Wearablesmentioning
confidence: 99%
“…In addition to being less cumbersome than Holter monitors, these chest-worn sensors may be easier to apply in remote settings compared to a sacral sensor when used for movement analysis. Cardiac measures, such as heart rate, have been shown to relate to disease severity and fatigue in PwMS [26] and may inform new measures of fatiguability [27]. Wide adoption of these devices, which often include accelerometers, may also provide an opportunity for expanding our ability to capture measures of postural sway using these devices, but chest-worn accelerometers have not yet been validated for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Commercially available wearable devices (wearables) and contactless technologies (nearables) are increasingly used for home monitoring and have the potential to enable remote health monitoring and promote independent living [11][12][13][14][15][16][17][18]. These technologies offer secure digital infrastructure that allows reliable and seamless transfer of collected data to cloud servers and can facilitate long term remote monitoring opportunities for healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…Wearables are widely used for continuous, community monitoring of heart rate and some have been evaluated in clinical settings although predominantly in younger age groups [17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation